2019
DOI: 10.1038/s41598-019-55463-6
|View full text |Cite
|
Sign up to set email alerts
|

A qPCR method for genome editing efficiency determination and single-cell clone screening in human cells

Abstract: CRISPR/Cas9 technology has been widely used for targeted genome modification both in vivo and in vitro. However, an effective method for evaluating genome editing efficiency and screening single-cell clones for desired modification is still lacking. Here, we developed this real time PCR method based on the sensitivity of Taq DNA polymerase to nucleotide mismatch at primer 3′ end during initiating DNA replication. Applications to CRISPR gRNAs targeting EMX1, DYRK1A and HOXB13 genes in Lenti-X 293 T cells exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 52 publications
0
41
0
Order By: Relevance
“…We previously reported that using primers with the tag-specific nucleotide placed at its 3’ end could achieve sequence-specific PCR quantification, and the nucleotide type of tag could significantly affect the PCR specificity [25]. To determine the best dinucleotide barcoding rule, we constructed 16 plasmids containing all the 16 kinds of dinucleotides using the coding sequence of the HOXB13 gene ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that using primers with the tag-specific nucleotide placed at its 3’ end could achieve sequence-specific PCR quantification, and the nucleotide type of tag could significantly affect the PCR specificity [25]. To determine the best dinucleotide barcoding rule, we constructed 16 plasmids containing all the 16 kinds of dinucleotides using the coding sequence of the HOXB13 gene ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3b and 3e). The potential mechanism that enables DST-PCR to detect these types of mutations is that the mismatched nucleotide at the primer 3' end was removed by the proofreading 3' to 5' exonuclease activity of the high-fidelity DNA polymerases [26][27][28] such as ExTaq DNA polymerase and KOD-Plus-Neo DNA polymerase during polymerizing and hence restored the PCR amplification capacity in part or completely. This means that DNA polymerases play an important role in deciding the discrimination ability of DST-PCR with high-fidelity DNA polymerase, increasing its ability in distinguishing the indels.…”
Section: Discussionmentioning
confidence: 99%
“…We then performed CRISPR/Cas9-mediated genome editing on the higher activity C allele in heterozygous MDA-MB-453 cells to test the direct regulatory effect of rs10514231 on gene expression. The genome-editing efficiency on the C allele was around 60%, as determined by the getPCR method [16] (Figure 3d). We analyzed the expression level of the three potential eQTL genes through RT-qPCR and found that only ATP6AP1L expression was affected by the genome-editing event and had a 40% reduction in the edited cells (Figure 3e-g).…”
Section: Rs10514231 Regulates the Expression Of Atp6ap1lmentioning
confidence: 91%
“…The medium was changed with the fresh medium containing 2 µg/mL puromycin 24 h later. After the non-transfected cells died completely, the survived transfected cells were passaged, with a part used for the editing efficiency evaluation using the getPCR method, as described previously [16]. Single-cell clones were isolated using the limited dilution method in 96-well plates, and the genotypes were determined by the getPCR assay and confirmed through Sanger sequencing.…”
Section: Genome Editing Using Crispr/cas9mentioning
confidence: 99%